GAGASAN TASAWUF KONTEKSTUAL K. H. HAMDANI BAKRAN ADZ DZAKIEY AL BANJARI - Muhammad Zainal Abidin (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2009)
The background of this paper is from the problem that happened on the relation between Islam and knowledge in the muslim contemporary discourse. The problem is the irrelevancy between Islamic knowledge and the challenges facing by muslim people today. To overcom the problem many inttelectual muslims suggest the solution. One of them in sufism field done by K. H. Hamdani Bakran Adz Dzakiey Al Banjary. The are some basic ideas from K. H. Hamdani to make a contextual sufism. Some of them, he named his idea with the prophetic intelligence as the name of his sufism; he also put the prophet Muhammad as the life model of his pschology. Actually, the idea of K. H. Hamdani is part of the current issue on Islamic contemporary discourse that to make Islam as the knowledge, and he did it in sufism field.